Facebook envy and well-being of emerging adults: Emotion regulation as a moderator - Ramizo, Maria Pamela C. (Animo Repository, 2017)
This study explored the moderating role of emotion regulation, which is composed of cognitive reappraisal and expressive suppression, in the relationship between Facebook envy and well-being of emerging adults. The participants were 308 emerging adults, aged 18-29, single, Filipino, Facebook user, college graduate, never been married, without a child, with work experience, does not act in the role of a parent, and not a breadwinner. Data was gathered through self-report questionnaires. Descriptive statistics, reliability analysis and moderation analysis were applied. Results show that Facebook envy is significantly and negatively correlated to well-being. Cognitive reappraisal moderates the relationship between Facebook envy and well-being wherein the relationship is weakened at medium and high levels of Facebook envy but not in low Facebook envy. Results from this study aim to bring awareness about the impact of Facebook use, particularly the development of Facebook envy, to the well-being of emerging adults and how emotion regulation can help alter possible negative effects.